Review on conductivity enhancement in n-ZnO/p-Si heterojunction diodes with the influence of Rare earth ions as donor impurities. - Ramachandran, Krithikadevi; Muthukumarasamy, Arulmozhi; Chidambaram, Siva; Gunarasan, Raamdheep (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Nanoelectronics is an emerging field of nanotechnology where innumerable nanomaterials are used to fabricate electronic devices like LEDs, Photodiodes, Transistors, FETs, UJTs, SCRs, Laser diodes, etc. The accomplishment of high-efficiency electronic devices at low cost tends to be the foremost challenging task in the field of nanoelectronics. The p-n heterojunction is a junction of two dissimilar p and n-type crystalline materials with different bandgap energies, work functions and electron affinities.The n-ZnO/p-Si heterojunction device tends to be cost-effective and also potential candidates for integration with microelectronic based photonic and optoelectronic devices. Th electrical properties of n-ZnO/p-Si heterojunction diode can be fine-tuned by the addition of dopants at different concentrations.This article presents a brief overview on the influence of different rare earth dopants on chargecarrier enhancement and transport mechanism in n-ZnO/p-Si heterojunction diode. This review paper also presents an outline on heterojunction formation theories and applications of n-ZnO/p-Si heterojunction diode